2023
DOI: 10.5817/cp2023-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptomatology is associated with problematic smartphone use severity in adolescents: The mediating role of cognitive emotion regulation strategies

Abstract: Problematic smartphone use (PSU) has been widely studied, and recent research has examined the affective and cognitive process risk factors that underlie its development and maintenance. Based on the Interaction of Person–Affect–Cognition–Execution model for problematic internet use, the present study analyzed the mediating role of cognitive emotion regulation strategies in the link between depressive symptomatology and PSU severity in adolescents. The sample consisted of 2,197 adolescents aged 12 to 19 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…[57][58][59] Relevant research has shown that high levels of depression in adolescents are an important factor contributing to smartphone addiction. 60 In summary, we hypothesize that harsh parenting can contribute to increased social pain which subsequently elevates levels of depression and ultimately leads to smartphone addiction. Accordingly, we proposed the following hypothesis.…”
Section: The Serial Mediating Role Of Social Pain and Depressionmentioning
confidence: 90%
See 2 more Smart Citations
“…[57][58][59] Relevant research has shown that high levels of depression in adolescents are an important factor contributing to smartphone addiction. 60 In summary, we hypothesize that harsh parenting can contribute to increased social pain which subsequently elevates levels of depression and ultimately leads to smartphone addiction. Accordingly, we proposed the following hypothesis.…”
Section: The Serial Mediating Role Of Social Pain and Depressionmentioning
confidence: 90%
“…Empirical studies have consistently demonstrated that depression constitutes a significant risk factor for smartphone addiction. 60 Building upon these findings, we propose the following hypothesis.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation